Poetic machinations : allegory, surrealism, and postmodern poetic form - Golston, Michael (New York : Columbia University Press, 2015)
The shape, lineation, and prosody of postmodern poems are extravagantly inventive, imbuing their form with as much meaning as their content. Through a survey of American poetry and poetics from the end of World War II to the present, Michael Golston traces the proliferation of these experiments to a growing fascination with allegory in philosophy, linguistics, critical theory, and aesthetics, introducing new strategies for reading American poetry while embedding its formal innovations within the history of intellectual thought. Beginning with Walter Benjamin's explicit understanding of Surrea.
""Table of Contents ""; ""Polemical Preface ""; ""Acknowledgments""; ""Introduction: Etymologies, 1980â€?the Allegorical Moment""; ""1. Entomologies: Louis Zukofsky and Lorine Niedecker""; ""2. Epistemologies: Clark Coolidge""; ""3. A=L=L=E=G=O=R=I=E=S: Peter Inman, Myung Mi Kim, Lyn Hejinian""; ""4. Semiologies: Susan Howe ""; ""5. Fictocritical Postlude: The Melancholy of Conceptualism""; ""Notes""; ""Works Cited""; ""Index""
Online resource; title from PDF title page (EBSCO, viewed October 6, 2015).
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: American poetry -- 20th century -- History and criticism; Allegory; Surrealism (Literature); Poetics; Poésie américaine -- 20e siècle -- Histoire et critique; Allégorie.; Surréalisme (Littérature); Poétique.; Surrealist; allegories (literary genre); LITERARY CRITICISM -- Poetry; Allegory; American poetry; Poetics; Surrealism (Literature); English; Languages & Literatures; American Literature; 1900-1999; Surrealism (Literature); Criticism, interpretation, etc